Making it so : a memoir [compact disc, unabridged] - Stewart, Patrick, 1940- (Simon & Schuster Audio, 2023)
"From his acclaimed stage triumphs to his legendary onscreen work in the Star Trek and X-Men franchises, Sir Patrick Stewart has captivated audiences around the world and across multiple generations with his indelible command of stage and screen. Now, he presents his long-awaited memoir, Making It So, a revealing portrait of an artist whose astonishing life -- from his humble beginnings in Yorkshire, England, to the heights of Hollywood and worldwide acclaim -- proves a story as exuberant, definitive, and enduring as the author himself" --